Assessing food appeal and desire to eat: the effects of portion size & energy density - Cornier Marc A; Burger Kyle S; Ingebrigtsen Jan; Johnson Susan L (International Journal of Behavioral Nutrition and Physical Activity, 2011)
Abstract Background Visual presentation of food provides considerable information such as its potential for palatability and availability, both of which can impact eating behavior. Methods We investigated the subjective ratings for food appeal and desire to eat when exposed to food pictures in a fed sample (n = 129) using the computer paradigm ImageRate. Food appeal and desire to eat were analyzed for the effects of food group, portion size and energy density of the foods presented as well as by participant characteristics. Results Food appeal ratings were significantly higher than those for desire to eat (57.9 ± 11.6 v. 44.7 ± 18.0; p < 0.05). Body mass index was positively correlated to desire to eat (r = 0.20; p < 0.05), but not food appeal. Food category analyses revealed that fruit was the highest rated food category for both appeal and desire, followed by discretionary foods. Additionally, overweight individuals reported higher ratings of desire to eat large portions of food compared to smaller portions (p < 0.001), although these effects were relatively small. Energy density of the foods was inversely correlated with ratings for both appeal and desire (r's = - 0.27; p's < 0.01). Conclusions Results support the hypothesis that individuals differentiate between food appeal and desire to eat foods when assessing these ratings using the same type of metric. Additionally, relations among food appeal and desire to eat ratings and body mass show overweight individuals could be more responsive to visual foods cues in a manner that contributes to obesity.